Fossil history of bark-beetles (Coleoptera: Scolytidae) with descriptions of two new species - Legalov, Andrei A. (Historical biology)
The presence of fossil bark beetles from the early Cretaceous to the Miocene is discussed. Changes in the diversity of this group over time are presented. Assumptions about trophic relationships are given. Two new species, Hylastes perkovskyi n. sp. from the tribe Hylastini and Chramesus boninoi n. sp. from the tribe Hylesinini, are described, respectively, from Eocene Rovno and Miocene Dominica amber. These are the first records of the genera Hylastes in Rovno amber and Chramesus in Dominican amber.